2023
DOI: 10.1590/01047760202329013135
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the efficiency of MaxEnt, topsis and invest models on site suitability and decline potential of Persian oak forests in Zagros, Iran (Ilam Province)

Abstract: Background: Over the last decade, a significant area of Zagros forests, especially in Ilam Province, west of Iran, has been affected by the phenomenon of oak decline. The most basic item for fighting the decline of these forests is to know site suitability, the parameters affecting it, determining the criteria affecting the decline and preparing a map of the decline potential of these forests. In this study, the efficiency of Maxent on preparing site suitability map of Dalab and Bankol and the most important c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(58 reference statements)
1
1
0
Order By: Relevance
“…Despite the tolerance of Persian oak species to the range of temperatures from − 31 to + 45 °C, the incidence of CD has increased dramatically in Q. brantii forests. Our results are in agreement with the studies conducted at regional scales 4 , 19 , 21 23 where oak forests were surveyed for CD incidence and pathogenicity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the tolerance of Persian oak species to the range of temperatures from − 31 to + 45 °C, the incidence of CD has increased dramatically in Q. brantii forests. Our results are in agreement with the studies conducted at regional scales 4 , 19 , 21 23 where oak forests were surveyed for CD incidence and pathogenicity.…”
Section: Discussionsupporting
confidence: 92%
“…SDMs have been defined as reliable models to predict the geographic distribution of rare species 55 . Albeit a total of selected 29 bioclimatic variables and applied models here were slightly different from those used in other local studies in CD distribution 4 , 23 , 56 – 60 , these parameters and models have shown high accuracy (ROC up to 96%) in CD modeling considering the extent of the study area, Zagros forests.…”
Section: Discussionmentioning
confidence: 96%